2018
DOI: 10.1002/pssr.201800493
|View full text |Cite
|
Sign up to set email alerts
|

Improved Negative‐Capacitance Switch of Ferroelectric Field Effect Transistor Using Defect Passivation Engineering

Abstract: A ferroelectric negative‐capacitance (NC) transistor using aluminum‐doped hafnium oxide (HfAlOx) with fluorine passivation is successfully demonstrated. The fluorine‐passivated device shows a nearly hysteresis‐free forward/reverse swing of sub‐30 mV dec−1 for symmetric switch, a wide sub‐60 mV (dec·swing)−1 range over 4 decades of drain current, an ultralow off‐leakage current of 4 fA μm−1, and a high on/off current ratio of >108. The fluorine defect passivation (FP) reduces oxygen vacancies of ferroelectric H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Clearly, the Zr 3d and Hf 4f peaks of the plasma-treated Hf 0.5 Zr 0.5 O 2 film are shifted to lower BE's (182.5 eV and 16.2 eV respectively) relative to those of the untreated Hf 0.5 Zr 0.5 O 2 film (183.1 eV and 16.4 eV respectively), implying a reduction of oxygen vacancies. This is beneficial to mitigating the depolarization field at the interface between Hf 0.5 Zr 0.5 O 2 and Al 2 O 3 , thus increasing the amplification effect on the surface potential of the MoS 2 channel during the NC operation in addition to reducing gate leakage path [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the Zr 3d and Hf 4f peaks of the plasma-treated Hf 0.5 Zr 0.5 O 2 film are shifted to lower BE's (182.5 eV and 16.2 eV respectively) relative to those of the untreated Hf 0.5 Zr 0.5 O 2 film (183.1 eV and 16.4 eV respectively), implying a reduction of oxygen vacancies. This is beneficial to mitigating the depolarization field at the interface between Hf 0.5 Zr 0.5 O 2 and Al 2 O 3 , thus increasing the amplification effect on the surface potential of the MoS 2 channel during the NC operation in addition to reducing gate leakage path [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Though much research has been done on NCFET [12][13][14][15][16], while investigations on NCFET based on GaAs substrate are still limited, much uncertainty still exists. For NCFET based on Silicon, it has been found that: (1) When channel length (LC) is increased, the gate voltage amplification (GVA) effect is weakened [17].…”
Section: Introductionmentioning
confidence: 99%